1995
DOI: 10.1016/0896-6273(95)90345-3
|View full text |Cite
|
Sign up to set email alerts
|

Widespread expression of Huntington's disease gene (IT15) protein product

Abstract: Huntington's Disease (HD) is caused by expansion of a CAG repeat within a putative open reading frame of a recently identified gene, IT15. We have examined the expression of the gene's protein product using antibodies developed against the N-terminus and an internal epitope. Both antisera recognize a 350 kDa protein, the predicted size, indicating that the CAG repeat is translated into polyglutamine. The HD protein product is widely expressed, most highly in neurons in the brain. There is no enrichment in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
271
1
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(285 citation statements)
references
References 51 publications
11
271
1
2
Order By: Relevance
“…1 In patients, progressive widespread brain atrophy, 2,3 leading to severe motor disability over time, is associated with early peripheral tissue dysfunction such as loss of body weight. 4,5 Hence, the pathological involvement of non-nervous tissues may contribute to the clinical features of HD.…”
Section: Introductionmentioning
confidence: 99%
“…1 In patients, progressive widespread brain atrophy, 2,3 leading to severe motor disability over time, is associated with early peripheral tissue dysfunction such as loss of body weight. 4,5 Hence, the pathological involvement of non-nervous tissues may contribute to the clinical features of HD.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The selectivity of neuronal death seen in HD striatum and cortex is remarkable given that huntingtin protein (Htt) is normally expressed throughout the central nervous system as well as in non-neuronal cells. [16][17][18] Htt is also widely distributed at the subcellular level and has been found within nuclei, perikarya, neurites, and synaptic elements. [16][17][18][19][20][21] Considering the widespread expression of Htt, it is interesting that the enkephalin and substance P-containing medium spiny neurons are vulnerable in the striatum, while large cholinergic and medium aspiny neurons are spared.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Htt is also widely distributed at the subcellular level and has been found within nuclei, perikarya, neurites, and synaptic elements. [16][17][18][19][20][21] Considering the widespread expression of Htt, it is interesting that the enkephalin and substance P-containing medium spiny neurons are vulnerable in the striatum, while large cholinergic and medium aspiny neurons are spared. 14,[22][23][24] In the cortex, the pyramidal cortical projection neurons in layers III and V are vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…Htt is a huge protein with a widespread distribution in neurons, including cell bodies, dendrites and axons (Sharp et al, 1995). Detailed subcellular fractionation and microscopic studies have shown that htt is also associated with vesicles and microtubules (Difiglia et al, 1995;Hoffner et al, 2002), where it interacts with molecular motors that promote the transport of vesicles containing brain derived-neurotrophic factor (BDNF) (Gauthier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%